Normal-temperature drying preparation method of graphene aerogel

Through the normal temperature drying method and the improved Hummers legal preparation graphene gas gel, it solves the problem of high preparation costs and difficult production of graphene gas gel in existing technologies, and realizes large -scale, high -performance graphene gas gel gel gels Preparation.

CN119349562APending Publication Date: 2025-01-24BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202411265437.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24

Smart Images

  • Figure CN119349562A_ABST
    Figure CN119349562A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano composite materials, in particular to a normal-temperature drying preparation method of graphene aerogel. Comprising the following steps: 1) preparing a graphene oxide dispersion liquid; 2) mixing the graphene oxide dispersion liquid obtained in the step 1) with a reinforcing agent, a reducing agent and a surface active foaming agent, sequentially performing heating, freezing and solvent replacement, and then performing normal-temperature drying to obtain pre-reduced composite graphene aerogel; and 3) performing high-temperature annealing on the pre-reduced composite graphene aerogel obtained in the step 3) to obtain the graphene aerogel. The invention provides a novel and simple method, micron-sized foam is adopted as a template, the large-area graphene aerogel is prepared through a conventional sol-gel method and is naturally dried at room temperature, the problem of structural cracking caused by stress concentration in large-area preparation of the aerogel is solved, supercritical drying is avoided, and the large-area graphene aerogel is obtained. And the problems of long period and cost caused by a freeze drying method are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanocomposite materials, and in particular to a method for preparing graphene aerogel by drying it at room temperature. Background Art

[0002] Driven by nanotechnology, the controllable assembly of nanomaterials into three-dimensional macroscopic materials can maximize their excellent physical and chemical properties and have a wide range of applications in energy storage, catalysis, sensing and conductive composite materials. Among them, porous aerogel materials have become one of the hot spots with their extremely low density, large specific surface area and adjustable pore structure. Graphene is a two-dimensional carbon material formed by a single layer of carbon atoms arranged in a hexagonal honeycomb shape. It has the characteristics of high strength, high elasticity and high conductivity, and is one of the ideal choices for preparing electromagnetic shielding aerogel materials.

[0003] Graphene aerogel is a highly porous and lightweight material composed of graphene flakes. It forms a three-dimensional network through a special structural arrangement and cross-linking method, showing the characteristics of light weight, excellent mechanical properties, environmental friendliness and multifunctionality. Although graphene aerogel has important application value in many high-tech fields due to its unique structure and properties, its industrial application still needs to solve challenges such as cost, manufacturing process and precise control of orientation and structural arrangement. Among them, the key problem to be solved is the low-cost preparation of graphene aerogel with thermal insulation, excellent mechanical properties and high shielding properties.

[0004] With the advancement of electronic communication technology and the complexity of the operating environment, the market demand for multifunctional equipment with high comprehensive performance has increased, including higher requirements for thermal management and mitigation of electromagnetic radiation and interference. At present, the commonly used drying methods are mainly freeze-drying and supercritical drying. However, the above methods are difficult to prepare large-area and complex-shaped graphene structures; and their preparation processes are energy-intensive or time-consuming, costly, and difficult to apply on a large scale. In addition, when the degree of reduction of graphene is high, the removal of oxygen-containing functional groups on the surface between its sheets weakens its structural stability, greatly affecting its application scenarios.

[0005] In order to meet these challenges, it is crucial to develop integrated materials with the characteristics of light weight, high mechanical strength, high thermal insulation and effective electromagnetic wave absorption. Among the potential materials, graphene aerogel has attracted widespread attention due to its advantages of large specific surface area, high porosity, excellent electrochemical properties, etc., which endow it with properties such as light weight, high conductivity, and superelasticity under extreme conditions. At present, in order to prepare graphene aerogels with various excellent properties, the commonly used measures generally require the addition of some polymer additives and GO to form a nanocomposite material, and then freeze drying / supercritical drying is used to transform the solid-liquid interface or gas-liquid interface into a solid-solid interface, eliminating the capillary force and ensuring the pore structure. For example, Chinese patent CN111945185B discloses a three-dimensional porous doped CNT graphene aerogel self-assembled by freeze drying or a specific reduction method using GO and carbon nanotubes (CNT) (the mass ratio of carbon nanotubes in the raw material is 9-11wt%) as raw materials, which has been applied in the field of electrode materials. Chinese patent CN216293082U discloses a method of preparing graphene aerogel by freeze-drying a 10 mg / mL graphene oxide solution and a needle-punched nonwoven fabric under liquid nitrogen. The above process is not only cumbersome, but also requires expensive equipment such as a supercritical dryer and a freeze dryer, which limits the scalability and large-scale production of aerogels.

[0006] In summary, developing a low-cost, efficient, and easy-to-mass-produce graphene aerogel preparation technology to meet the demand for high-performance integrated materials in fields such as electronic communications has become a technical challenge that needs to be solved urgently.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The present invention aims to solve the problems in the prior art and proposes a method for preparing graphene aerogel by drying at room temperature. Natural drying under ambient conditions provides a streamlined method in which liquid evaporates directly from the hydrogel to produce an aerogel with minimal deformation. This method ensures industrial-scale production efficiency without compromising structural integrity; it simply and efficiently realizes the preparation of large-area graphene aerogels with excellent electrical conductivity, electromagnetic shielding and thermal insulation properties.

[0009] To achieve the above objectives, the present invention adopts the following technical solutions.

[0010] The present invention provides a method for preparing graphene aerogel by drying at room temperature, comprising the following steps:

[0011] 1) preparing a graphene oxide dispersion;

[0012] 2) mixing the graphene oxide dispersion obtained in step 1) with a reinforcing agent, a reducing agent and a surfactant foaming agent, heating, freezing, and solvent replacement in sequence, and then drying at room temperature to obtain a pre-reduced composite graphene aerogel;

[0013] 3) annealing the pre-reduced composite graphene aerogel obtained in step 3) at high temperature to obtain graphene aerogel.

[0014] Preferably, in step 1), the concentration of the graphene oxide dispersion is 12 mg / mL to 20 mg / mL.

[0015] Preferably, in step 2), the solid content of the reinforcing agent is 5wt% to 10wt% of the solid content of the graphene oxide dispersion in the solution;

[0016] The ratio of the solid content of the reducing agent to the solid content of the graphene oxide dispersion in the solution is 0.75 to 1:1;

[0017] The ratio of the solid content of the surfactant foaming agent to the sum of the solid content of the graphene oxide dispersion in the solution and the solid content of the reinforcing agent is 5 / 6 to 1:1.

[0018] Preferably, in step 2), the graphene oxide dispersion, reinforcing agent, surfactant foaming agent and reducing agent are mixed at a rotation speed of 600 to 5000 rpm for 10 to 20 minutes.

[0019] Preferably, in step 2), the reinforcing agent comprises one or more of a water-soluble polyamic acid (PAA) solution, cellulose nanofibers (CNF) and polyvinyl alcohol (PVA);

[0020] The reducing agent includes one or more of ascorbic acid, hydrazine hydrate (N2N4) and ethylenediamine (EDA);

[0021] The surface active foaming agent includes one or more of sodium dodecyl sulfate (SDS), alkyl polyglycoside (APG) and fatty alcohol polyoxyethylene ether (AEO).

[0022] Preferably, in step 2), heating: the hydrothermal temperature is 70 to 100° C.; the hydrothermal reaction time is 9 to 12 hours;

[0023] The freezing temperature is -30 to -15°C and the freezing time is 20 to 25 hours;

[0024] The solvent exchange temperature is 20-28°C;

[0025] The temperature for room temperature drying is 20-28°C.

[0026] Preferably, in step 2), the exchange solvent of the solvent exchange comprises one of methanol, ethanol or isobutanol.

[0027] Preferably, in step 3), the temperature of the high temperature annealing is 800-1600°C.

[0028] Preferably, the graphene aerogel has a microporous structure with an average pore diameter of 10 to 250 μm.

[0029] Preferably, the graphene aerogel has one or more of the following properties:

[0030] Conductivity is 400~1000S / m;

[0031] Thermal conductivity is 25-50 mW / m·K;

[0032] Area larger than 30*30cm 2 ;

[0033] At frequencies of 2 to 40 GHz, the electromagnetic shielding rate is 90 to 120 dB at a thickness of 4 to 9 mm;

[0034] Density 8~18mg / cm 3 of;

[0035] Superelasticity and fatigue resistance at 77K in extreme environments are greater than >95%.

[0036] Specifically, the present invention relates to a method for preparing graphene aerogel by drying at room temperature, comprising the following steps: firstly, a graphene oxide (GO) aqueous dispersion is synthesized by an improved Hummers method. Then, the GO dispersion with a volume of V1 is uniformly mixed with a reinforcing agent with a volume of V2, a reducing agent with a mass of M1, and a surfactant foaming agent with a mass of M2 under the action of a disperser, and then poured into a mold, followed by a series of treatments such as hydrothermal reaction and freezing, and finally dried at room temperature to obtain a pre-reduced GO aerogel, and the GO aerogel is subjected to high-temperature annealing to achieve the preparation of a large-area graphene aerogel with light weight, superelasticity and fatigue resistance stability under extreme temperature conditions, and excellent electromagnetic shielding, and at the same time, the phenomenon of easy fracture caused by the brittle layer structure due to stress concentration under large-area conditions is solved.

[0037] The present invention selects the polyimide (PI) interface enhancement strategy to integrate the three-dimensional network of the entire aerogel material, effectively enhancing the connection of the sheets. In the present invention, the strong interaction between the enhancer molecules and the hydrophilic GO sheets forms a solid 3D structure, giving the skeleton significant high reversible compressibility and tensile properties. For example, the enhancer water-soluble PAA solution, PAA is thermally imidized at high temperature to obtain PI during the high-temperature reduction process, and the PI molecular chain forms rGO under the action of high temperature to form more polar forces such as hydrogen bonds, thereby improving the mechanical properties of the prepared graphene aerogel. The reducing agent of the present invention removes the oxidized functional groups on the surface of GO, converts the hydrophilic GO into hydrophobic reduced graphene oxide, enhances the π-π conjugation effect, and enhances the sheet effect, preferably but not limited to green and non-toxic ascorbic acid (VC) and the like. The surfactant of the present invention forms micron-sized foam with GO / enhancer. For example, at high speed, a large amount of air is introduced into the GO / PAA solution under the action of the surfactant sodium dodecyl sulfate to form a micron-sized emulsified foam. These bubbles exclude GO sheets and PAA well and cross-link around the bubbles to form a strong network structure, preferably but not limited to green anionic surfactant sodium dodecyl sulfate (SDS) and the like.

[0038] In the present invention, the high concentration GO dispersion can provide strong support, which is more conducive to the preparation of a large area. Therefore, the present invention uses a GO dispersion with a concentration of 12 mg / mL to 20 mg / mL. Due to Ostwald ripening, the bubbles are unstable. The chemical reduction of graphene oxide introduces π-π stacking and agglomeration of graphene, forming a three-dimensional structure, restricting the movement of bubbles and ensuring the stability of the bubble structure.

[0039] The GO nanosheets in the water phase of the present invention are self-assembled around micron-sized bubbles after adding a reducing agent and a surfactant, and then hydrothermally reduced, and then naturally dried after solvent replacement after freezing. According to the Laplace equation: Wherein Δp is the capillary force, θ is the contact angle between the interface of the solution and the pore wall, γ is the surface tension in the capillary, and r is the capillary radius. The main method to ensure natural drying is that when the volume shrinks, the stiffness of the nanosheet skeleton must be able to withstand the Δp generated by solvent evaporation. In general, the skeleton stiffness mainly depends on the structure and performance of the assembly unit, such as the interconnectivity and thickness of the pore wall. At the same time, it can be seen from the formula that Δp can be determined by γ, θ and r. Reducing Δp can be achieved by optimizing the solvent type, changing the hydrophilicity and hydrophobicity of the skeleton and the size of the pore structure. In order to ensure the successful implementation of natural drying, the present invention removes the functional groups on the surface of GO by adding a reducing agent, converts the hydrophilic GO nanosheets into hydrophobic reduced graphene oxide (rGO), enhances the π-π conjugated force between the nanosheet layers, inhibits Ostwald ripening, enhances the stiffness of the sheet layers, and the hydrophobicity also enhances the contact angle of rGO with water. The surfactant reduces the surface energy and ensures that the pores will not collapse to the greatest extent. At the same time, the introduction of microbubbles is not easy to collapse compared to nanobubbles. Thus, we can get 40*30cm 2 , electromagnetic shielding is greater than 100dB, and the density is only 10mg / cm 3 Large-area graphene aerogel.

[0040] Beneficial effects of the present invention:

[0041] The present invention provides a novel and simple method, which adopts micron-sized foam as a template, prepares large-area graphene aerogel by a conventional sol-gel method and dries it naturally at room temperature, thereby solving the problem of structural cracking caused by stress concentration in the large-area preparation of aerogel and avoiding the long cycle and cost problems caused by supercritical drying and freeze-drying methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1(a) is a top view of graphene aerogel, showing its stable structure;

[0044] Figure 1(b) is a graph showing the length of graphene aerogel, showing that its length is greater than 30 cm;

[0045] Figure 1(c) is a graph showing the width of the graphene aerogel, showing that its width is greater than 30 cm;

[0046] Figure 1(d) shows graphene aerogels in different embodiments, showing that their size is greater than 30 cm;

[0047] Figure 2(a) is a scanning electron microscope image of graphene aerogel magnified ×30 times, showing the pore structure at various levels;

[0048] Figure 2(b) is a scanning electron microscope image of graphene aerogel magnified ×1200 times, showing the pore structure at various levels;

[0049] Figure 2(c) is a scanning electron microscope image of the graphene aerogel magnified ×400 times, showing the pore structure at various levels;

[0050] Figure 2(d) is a scanning electron microscope image of the graphene aerogel magnified ×200 times, showing the pore structure at various levels;

[0051] Figure 3 The thermal conductivity of aerogels treated at 25°C, 180°C, and 1000°C are shown;

[0052] Figure 4 (a) shows the stress-strain curve of graphene aerogel in liquid nitrogen environment and 1000 cycles of mechanical rebound test, showing excellent mechanical properties;

[0053] Figure 4(b) shows the stress-strain curve of graphene aerogel at room temperature and 1000 cycles of mechanical rebound test, showing excellent mechanical properties;

[0054] Figure 5(a) shows the electromagnetic shielding performance of graphene aerogel after annealing at 1000°C;

[0055] Figure 5(b) shows the electromagnetic shielding performance of graphene aerogel after annealing at 1600°C;

[0056] Note: The 25℃ and 180℃ in the attached figure are both control groups. DETAILED DESCRIPTION

[0057] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0058] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0059] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0060] In this specification, the term "room temperature" or "normal temperature" refers to an ambient temperature of 20-28°C.

[0061] In this specification, the concentration error used is no more than ±2%.

[0062] In this manual, the mass error used does not exceed ±0.5g.

[0063] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0064] The present invention will be further described in detail below through specific implementation examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0065] Furthermore, the present invention provides a method for preparing graphene aerogel by drying at room temperature, and proposes a polyimide interface enhancement strategy assisted by a micron-sized bubble template and an ice template, thereby obtaining a large-area graphene aerogel, wherein the micron-sized bubble template is a solution rotating at a high speed, and air is introduced into the solution under the action of a surfactant to form bubbles; the ice template is a sample after hydrothermal treatment put into a refrigerator to freeze water into ice, and ice crystals grow and extrude graphene oxide nanosheets at a temperature of -30 to -15°C. The specific method is as follows:

[0066] (1) Preparation of GO homogeneous dispersion

[0067] The graphene oxide solution is prepared by using the improved Hummers method, which is a conventional technical means in the art, and the specific steps are as follows:

[0068] Low-temperature reaction stage: add 23 mL of concentrated sulfuric acid into a 250 mL beaker and seal it with plastic wrap. Stir magnetically for 5 min (800 rpm) in an ice-water bath. At this time, the concentrated sulfuric acid is cooled to -1 to 1 °C. Then slowly add 1 g of natural graphite (5000 mesh) and stir at 1000 rpm for 30 min. Then, at 1500 rpm, slowly add 6 g of KMnO4 in about 15 min and stir for 2.5 h.

[0069] Medium temperature reaction stage: Take the large beaker out of the ice water and place it in a constant temperature water bath at 40°C, and stir mechanically at 300rpm for 20min; adjust the water bath temperature to 80°C, and program the water bath to heat up (this process takes about 40min). High temperature reaction stage: After the water bath is heated to 80°C, adjust the speed to 400rpm, and then very slowly add 80mL of distilled water in about 15min (first very slowly drop, then gradually increase the drop speed); continue stirring for 15min, add 60mL of distilled water to dilute, and then pour a mixed solution consisting of 10.81mL of 30% H2O2 and 60mL of distilled water along the glass rod. When the beaker appears golden yellow and slightly red, take out the solution immediately and centrifuge it with deionized water to wash it until the pH value is about 5 to 6, and obtain a graphene oxide solution. The reason why natural graphite with a mesh size of 5000 is selected as the raw material is that graphite is more easily oxidized at this scale, and the diameter of the graphene oxide flakes obtained after exfoliation is smaller, which is conducive to the development of subsequent research. The above operation is repeated to obtain graphene oxide slurry.

[0070] Determination of the concentration of graphene oxide solution: take a clean coverslip and weigh its mass (accurate to 0.0001g) recorded as m1, drop an appropriate amount of graphene oxide solution on the coverslip, weigh its mass, recorded as m2, place the coverslip containing graphene oxide solution in a vacuum oven until the mass of the coverslip no longer changes, record its mass as m3, the concentration of graphene oxide solution can be calculated using the following formula: C = (m3-m1) / (m2-m1)ρ, ρ is the density of water.

[0071] (2) Preparation of graphene aerogel

[0072] The prepared GO dispersion was prepared into 12-20 mg / mL, and a reinforcing agent was added to form a sol (the reinforcing agent was 5%-20% of the mass of GO), the mixed dispersion of GO and the reinforcing agent was ultrasonicated for 30 minutes, and a reducing agent (mass ratio of reducing agent: GO = 0.75-1:1) was added for pre-reduction, and the mixture was stirred at a high speed of 2000-3000 rpm for 5 minutes, and then a surfactant (the surfactant was 5 / 6-1 of the solid content of GO and the reinforcing agent) was added, and the mixture was stirred at a high speed of 3000-4000 rpm for 15 minutes. A uniform brown emulsified foam solution was obtained. Pour into a 40cm*30cm mold, shake evenly, put into an oven at 80-90°C for 9-12h to partially reduce the GO sheets and form a hydrogel, then put into a freezer for 20-25h to guide the ice crystal growth to extrude the graphene oxide nanosheets, then wash with water several times to wash out the reducing agent and surfactant, then immerse in anhydrous ethanol to replace the water, and place at room temperature to dry to obtain a partially reduced GO aerogel with a regular morphology and large area. Put it into a kiln and heat-treat it at 800-1000°C in an Ar atmosphere for 1-2h to obtain a large and regular graphene aerogel.

[0073] Example 1

[0074] First, the GO prepared by the Hummers method was concentrated to obtain a high-concentration graphene oxide filter cake of 400 mg / mL. Then, 50 g of the GO filter cake was added to 1250 mL of ultrapure water, 10% wt of PAA was added, and then ultrasonic dispersion was performed. 20.0 g of VC was added to the above dispersion, and it was evenly dispersed with the dispersion at a high speed of 3000 rpm for 5 min. Then, 15 g of SDS was added and vigorously stirred at 4000 rpm for 10 min to obtain an emulsified foam solution. The foam solution was poured into a 420 mm × 380 mm square mold, sealed and placed in an 80 ° C blast oven for 9 h of hydrothermal reaction to partially reduce the GO sheet layer and obtain a large area GO / PAA hydrogel with a thickness of 1 cm. It was placed in a -18 ° C freezer for 24 h, and then the solvent was replaced with anhydrous ethanol, and then placed at room temperature for natural drying to obtain a regular morphology pre-reduced GO / PAA aerogel. It was placed in a high temperature atmosphere box furnace at 1000°C under Ar atmosphere to obtain the final graphene aerogel.

[0075] Example 2

[0076] First, the GO prepared by the Hummers method was concentrated to obtain a high-concentration graphene oxide filter cake of 400 mg / mL. Then, 50 g of the GO filter cake was added to 1250 mL of ultrapure water, 10% wt of PAA was added, and then ultrasonic dispersion was performed. 20.0 g of VC was added to the above GO dispersion, and it was evenly dispersed with the dispersion at a high speed of 3000 rpm for 5 min. Then, 15 g of SDS was added and vigorously stirred at 4000 rpm for 10 min to obtain an emulsified foam solution. The foam solution was poured into a 420 mm × 380 mm square mold, sealed and placed in an 80 ° C blast oven for 9 h of hydrothermal reaction to partially reduce the GO sheet layer to obtain a large area GO / PAA hydrogel with a thickness of 1 cm. It was placed in a -18 ° C freezer for 24 h, and then the solvent was replaced with anhydrous ethanol, and then placed at room temperature for natural drying to obtain a regular morphology pre-reduced GO / PAA aerogel. It was placed in a high temperature atmosphere box furnace at 1600°C under Ar atmosphere to obtain the final graphene aerogel.

[0077] Example 3

[0078] First, the GO prepared by the Hummers method was concentrated to obtain a 400 mg / mL high-concentration graphene oxide filter cake, and then 56.25 g of the GO filter cake was added to 1250 mL of ultrapure water, 10% wt of PAA was added, and then ultrasonic dispersion was performed, 20.0 g of VC was added to the GO dispersion, and the mixture was uniformly dispersed with the dispersion at a high speed of 3000 rpm for 5 min, and then 20 g of SDS was added, and the mixture was vigorously stirred at a speed of 4000 rpm for 10 min to obtain an emulsified foam solution. The subsequent process was the same as the subsequent process in Example 1.

[0079] Example 4

[0080] First, the GO prepared by the Hummers method was concentrated to obtain a 400 mg / mL high-concentration graphene oxide filter cake, and then 56.25 g of the GO filter cake was added to 1250 mL of ultrapure water, 10% wt of PAA was added, and then ultrasonic dispersion was performed, 20.0 g of VC was added to the GO dispersion, and the mixture was uniformly dispersed with the dispersion at a high speed of 3000 rpm for 5 min, and then 20 g of SDS was added, and the mixture was vigorously stirred at a speed of 4000 rpm for 10 min to obtain an emulsified foam solution. The subsequent process was the same as the subsequent process in Example 2.

[0081] Example 5

[0082] First, the GO prepared by the Hummers method was concentrated to obtain a 400 mg / mL high-concentration graphene oxide filter cake, and then 50 g of the GO filter cake was added to 1250 mL of ultrapure water, 10% wt of PAA was added, and then ultrasonic dispersion was performed, 20.0 g of VC was added to the GO dispersion, and the mixture was uniformly dispersed with the dispersion at 3000 rpm for 5 min, and then 20 g of SDS was added, and the mixture was vigorously stirred at 4000 rpm for 10 min to obtain an emulsified foam solution. The subsequent process was the same as the subsequent process in Example 1.

[0083] Example 6

[0084] First, the GO prepared by the Hummers method was concentrated to obtain a 400 mg / mL high-concentration graphene oxide filter cake, and then 56.25 g of the GO filter cake was added to 1250 mL of ultrapure water, 10% wt of PAA was added, and then ultrasonic dispersion was performed, 20.0 g of VC was added to the GO dispersion, and the mixture was uniformly dispersed with the dispersion at a high speed of 3000 rpm for 5 min, and then 20 g of SDS was added, and the mixture was vigorously stirred at a speed of 4000 rpm for 10 min to obtain an emulsified foam solution. The subsequent process was the same as the subsequent process in Example 1.

[0085] Example 7

[0086] First, the GO prepared by the Hummers method was concentrated to obtain a 400 mg / mL high-concentration graphene oxide filter cake, and then 50 g of the GO filter cake was added to 1250 mL of ultrapure water, 10% wt of PAA was added, and then ultrasonic dispersion was performed, and then 20.0 g of VC was added to the above GO dispersion, and the mixture was uniformly dispersed with the dispersion at a high speed of 3000 rpm for 5 min, and then 15 g of APG was added, and the mixture was vigorously stirred at a speed of 4000 rpm for 10 min to obtain an emulsified foam solution. The subsequent process was the same as the subsequent process in Example 1.

[0087] Example 8

[0088] First, the GO prepared by the Hummers method was concentrated to obtain a 400 mg / mL high-concentration graphene oxide filter cake, and then 50 g of the GO filter cake was added to 1250 mL of ultrapure water, 20% wt of CNF was added, and then ultrasonic dispersion was performed, and then 20.0 g of VC was added to the GO dispersion, and the mixture was uniformly dispersed with the dispersion at a high speed of 3000 rpm for 5 min, and then 15 g of SDS was added, and the mixture was vigorously stirred at a speed of 4000 rpm for 10 min to obtain an emulsified foam solution. The subsequent process was the same as the subsequent process in Example 1.

[0089] Example 9

[0090] First, the GO prepared by the Hummers method was concentrated to obtain a high-concentration graphene oxide filter cake of 400 mg / mL, and then 50 g of the GO filter cake was added to 1250 mL of ultrapure water, 10% wt of PAA was added, and then ultrasonic dispersion was performed. Then 20.0 g of EDA was added to the above GO dispersion, and it was evenly dispersed with the dispersion at a high speed of 3000 rpm for 5 min. Then 15 g of SDS was added and vigorously stirred at 4000 rpm for 10 min to obtain an emulsified foam solution. The foam solution was poured into a 420 mm × 380 mm square mold, sealed and placed in an 80 ° C blast oven for 12 h of hydrothermal treatment to partially reduce the GO layer to obtain a large-area GO / PAA hydrogel with a thickness of 1 cm. The subsequent process is the same as in Example 1.

[0091] Implementation Results

[0092] For Example 1, the density is 8.2 mg / cm 3 , conductivity 503S / m, electromagnetic shielding performance 96dB, thermal insulation performance 38mW m -1 K -1 .

[0093] For Example 2, the density is 6.9 mg / cm 3 , conductivity 841S / m, electromagnetic shielding performance 111dB, thermal insulation performance 50mW m -1 K -1 .

[0094] For Example 3, the density is 9.1 mg / cm 3 , conductivity 684S / m, electromagnetic shielding performance 101dB, thermal insulation performance 41mW m -1 K -1 .

[0095] For Example 4, the density is 7.2 mg / cm 3 , conductivity 922S / m, electromagnetic shielding performance 102dB, thermal insulation performance 55mW m -1 K -1

[0096] For Example 5, the density is 8.4 mg / cm 3 , conductivity 748S / m, electromagnetic shielding performance 108dB, thermal insulation performance 36mW m -1 K -1 .

[0097] For Example 6, the density is 11.1 mg / cm 3 , conductivity 555S / m, electromagnetic shielding performance 100dB, thermal insulation performance 42mWm -1 K-1 .

[0098] For Example 7, the density is 8.1 mg / cm 3 , conductivity 605S / m, electromagnetic shielding performance 103dB, thermal insulation performance 35mW m -1 K -1 .

[0099] For Example 8, the density is 9.7 mg / cm 3 , conductivity 644S / m, electromagnetic shielding performance 106dB, thermal insulation performance 42mW m -1 K -1 .

[0100] For Example 9, the density is 14.1 mg / cm 3 , conductivity 482S / m, electromagnetic shielding performance 97dB, thermal insulation performance 40mW m -1 K -1 .

[0101] The relevant process parameters in the above-mentioned electromagnetic shielding test method are as follows: the electromagnetic shielding effectiveness in the X-band is tested using a waveguide method, which is a conventional technical means in this field.

[0102] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0103] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing graphene aerogel by drying at room temperature, comprising the following steps: 1) preparing a graphene oxide dispersion; 2) mixing the graphene oxide dispersion obtained in step 1) with a reinforcing agent, a reducing agent and a surfactant foaming agent, heating, freezing, and solvent replacement in sequence, and then drying at room temperature to obtain a pre-reduced composite graphene aerogel; 3) annealing the pre-reduced composite graphene aerogel obtained in step 3) at high temperature to obtain graphene aerogel.

2. The normal temperature drying preparation method according to claim 1, characterized in that: In step 1), the concentration of the graphene oxide dispersion is 12 mg / mL to 20 mg / mL.

3. The normal temperature drying preparation method according to claim 1, characterized in that: In step 2), the solid content of the reinforcing agent is 5wt% to 10wt% of the solid content of the graphene oxide dispersion in the solution; The ratio of the solid content of the reducing agent to the solid content of the graphene oxide dispersion in the solution is 0.75-1:1; The ratio of the solid content of the surfactant foaming agent to the sum of the solid content of the graphene oxide dispersion in the solution and the solid content of the reinforcing agent is 5 / 6 to 1:

1.

4. The normal temperature drying preparation method according to claim 1, characterized in that: In step 2), the graphene oxide dispersion, reinforcing agent, surfactant foaming agent and reducing agent are mixed at a rotation speed of 600 to 5000 rpm for 10 to 20 minutes.

5. The normal temperature drying preparation method according to claim 1, characterized in that: In step 2), the reinforcing agent includes one of a water-soluble polyamic acid solution, cellulose nanofibers or polyvinyl alcohol; The reducing agent includes one of ascorbic acid, hydrazine hydrate or ethylenediamine; The surface active foaming agent includes one of sodium lauryl sulfate, alkyl glycoside or fatty alcohol polyoxyethylene ether.

6. The preparation method according to claim 1, characterized in that: In step 2), heating: the hydrothermal temperature is 70 to 100° C.; the hydrothermal reaction time is 9 to 12 hours; The freezing temperature is -30 to -15°C and the freezing time is 20 to 25 hours; The solvent exchange temperature is 20-28°C; The temperature for room temperature drying is 20-28°C.

7. The normal temperature drying preparation method according to claim 1, characterized in that: In step 2), the exchange solvent of the solvent exchange includes one of methanol, ethanol or isobutanol.

8. The normal temperature drying preparation method according to claim 1, characterized in that: In step 3), the temperature of the high temperature annealing is 800-1300°C.

9. The normal temperature drying preparation method according to claim 1, characterized in that: The graphene aerogel has a microporous structure with an average pore diameter of 10 to 250 μm.

10. The normal temperature drying preparation method according to claim 1, characterized in that: The graphene aerogel has one or more of the following properties: Conductivity is 400~1000S / m; Thermal conductivity is 25-50 mW / m·K; Area larger than 30*30cm 2 ; At frequencies of 2 to 40 GHz, the electromagnetic shielding rate is 90 to 120 dB at a thickness of 4 to 9 mm; Density 8~18mg / cm 3 ; Superelasticity and fatigue resistance at 77K in extreme environments are greater than >95%.

Citation Information

Patent Citations

  • Graphene aerogel working electrode materials and their preparation methods, graphene aerogel working electrodes and their applications

    CN111945185B

  • Graphene aerogel jacket

    CN216293082U

  • Redispersable nanoparticle powder material preparation method

    CN103214586A

  • High-performance graphene / cellulose composite hydrogel and aerogel and preparation methods thereof

    CN103937010A

  • Method for preparing isotropic superelastic graphene aerogel

    CN106517160A

Cited By

  • Graphene-based multifunctional aerogel material as well as preparation method and application thereof

    CN121342473A